Loop Diuretics Inhibit Ischemia-Induced Intracellular Ca2+ Overload in Neurons via the Inhibition of Voltage-Gated Ca2+ and Na+ Channels - Katnik, Christopher; Cuevas, Javier (Frontiers in Pharmacology, 2021)
One consequence of ischemic stroke is disruption of intracellular ionic homeostasis. Intracellular overload of both Na+ and Ca2+ has been linked to neuronal death in this pathophysiological state. The etiology of ionic imbalances resulting from stroke-induced ischemia and acidosis includes the dysregulation of multiple plasma membrane transport proteins, such as increased activity of sodium-potassium-chloride cotransporter-1 (NKCC-1). Experiments using NKCC1 antagonists, bumetanide (BMN) and ethacrynic acid (EA), were carried out to determine if inhibition of this cotransporter affects Na+ and Ca2+ overload observed following in vitro ischemia-acidosis. Fluorometric Ca2+ and Na+ measurements were performed using cultured cortical neurons, and measurements of whole-cell membrane currents were used to determine target(s) of BMN and EA, other than the electroneutral NKCC-1. Both BMN and EA depressed ischemia-acidosis induced [Ca2+]i overload without appreciably reducing [Na+]i increases. Voltage-gated Ca2+ channels were inhibited by both BMN and EA with half-maximal inhibitory concentration (IC50) values of 4 M and 36 M respectively. Similarly, voltage-gated Na+ channels were blocked by BMN and EA with IC50 values of 13 M and 30 M, respectively. However, neither BMN nor EA affected currents mediated by acid-sensing ion channels or ionotropic glutamatergic receptors, both of which are known to produce [Ca2+]i overload following ischemia. Data suggest that loop diuretics effectively inhibit voltage-gated Ca2+ and Na+ channels at clinically relevant concentrations, and block of these channels by these compounds likely contributes to their clinical effects. Importantly, inhibition of these channels, and not NKCC1, by loop diuretics reduces [Ca2+]i overload in neurons during ischemia-acidosis, and thus BMN and EA could potentially be used therapeutically to lessen injury following ischemic stroke.